Knowledge, Attitudes, and Practices of Urban Residents Toward COVID-19 in Shaanxi During the Post-lockdown Period - Xu, Na; Zhang, Yongai; Zhang, Xiaona; Zhang, Guangwei; Guo, Zikai; Zhao, Nan; Li, Fei (Frontiers in Public Health, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic in China is essentially under control. Under global scrutiny, China has started reviving the social, cultural, and working lives of its inhabitants. However, localized outbreaks of COVID-19 are occurring, indicating that the country still needs to follow disease prevention and control measures. Previous studies have assessed the knowledge, attitudes, and behaviors of the general public in China regarding COVID-19 during the pandemic. However, little is known about knowledge, attitudes, and practices (KAP) of Chinese residents regarding COVID-19 post-lockdown. Therefore, this study was conducted to identify the KAP and other factors among the residents of Shaanxi Province during the post-lockdown period. Methods: A cross-sectional, network questionnaire survey was conducted in Shaanxi Province from October 1–30, 2020. A total of 1,175 urban residents were interviewed via Wen Juan Xing, an online questionnaire tool. A self-developed online KAP COVID-19 questionnaire was developed in this study. The questionnaire consisted of four parts: general information, knowledge, attitude, and practice. Descriptive statistics and binomial logistic regression analysis were used in the statistical analysis. Results: The majority of the participants were knowledgeable about COVID-19. They had optimistic attitudes and behaved appropriately towards COVID-19. Education was the predictor for the knowledge of residents. Attitudes were more positive in residents who lived with elderly people, women, and children. Practices significantly correlated with attitudes, age, and education. Conclusion: We found that the KAP of residents in Shaanxi was at a relatively high level during the post-lockdown period. Although the lockdown was lifted, the epidemic is not over. Thus, it is necessary to develop targeted health education programs for residents with different demographic characteristics in Shaanxi.